Triple-Porosity and Dual-Permeability Productivity Prediction Model of CBM Wells Considering Complex Flow Regimes - Xiao, Qianhua; Wang, Huailin; Yang, Yanhui; Li, Zhiqiang; Jiang, Bocai; Li, Jiahao; Xiang, Zuping (Frontiers in Earth Science, 2022)
The productivity evaluation of CBM wells can yield significant insights in exploring the patterns of CBM production, predicting the effectiveness of the CBM well and reservoir stimulation , optimizing the gas reservoir development program and develop a reasonable production system, for the purpose of facilitating efficient development of CBM. In particular, to accurately evaluate CBM productivity , we should establish the corresponding mathematical model of fluid flow through porous media and productivity evaluation model based on a clear understanding of CBM occurrence states and mechanisms of its flow through porous media. After considering the effects of slip flow, Knudsen diffusion, surface diffusion, stress sensitivity and matrix shrinkage on fluid mass transfer, we have put forward a triple-porosity & dual-permeability mathematical model for predicting CBM productivity that incorporates matrix gas desorption, complex flow in matrix pores and gas-water two-phase flow in cleat system. At the same time, in combination with reservoir characteristic parameters and a case study of Ma-26 well in Ma Bidong block in the south of Qinshui Basin, we carried out a numerical simulation of the productivity of fractured CBM well, and analyzed the effects (on production performance) of occurrence states, cleat system permeability, complex flow regimes in matrix, Langmuir pressure and volume. The results show that a) a drop in pore pressure increases the effect of slip flow and diffusion flow, thus improving the matrix equivalent permeability (apparent permeability); b) in the initial drainage and production stage of CBM wells, both free gas and adsorbed gas are produced at the same time, while adsorbed gas dominates the production in later stages; c) the peak output and cumulative output of CBM wells increase significantly with the rise in cleat system permeability; d) The increase of Langmuir pressure, volume and matrix porosity are conducive to the increase of CBM production. The research has considerable reference value for work on mechanisms of CBM flow in porous media and post-fracking productivity evaluation of CBM, and also provides a theoretical basis for fieldwork in CBM development.